Meninjau Flexible Working Space (FWS) sebagai Pendekatan Baru di Kementerian Keuangan - Lestari, Amalia; Maritza A, Kayla Issaura; Hisam, M. Nizar; Anaswa, Siti Hajar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The growing flexible work trend marks a fundamental shift in the work paradigm in the modern era. Flexibility in the work environment is becoming increasingly important, especially in public sector organizations, to increase employee productivity and well-being. The Ministry of Finance, as a government institution responsible for public financial management, is also not immune from the need to adapt to these changes. This research aims to review the implementation of Flexible Working Space (FWS) as a new approach at the Ministry of Finance to improve employee efficiency and welfare. The research method used is a qualitative research method with a case study research approach. The research results show that the implementation of FWS in the Ministry has had a positive impact, such as increasing work flexibility and balance between employees' work and personal lives (work-life balance). However, challenges such as adapting to long-established work culture, performance and productivity management, how to maintain and increase a sense of togetherness and collaboration among employees, as well as data and information security issues still need to be addressed. Thus, implementing FWS in the Ministry of Finance can be an effective approach to improving organizational performance and employee welfare, but requires careful strategies in overcoming the associated challenges.